Prediction of Molecular Mechanisms for LianXia NingXin Formula: A Network Pharmacology Study - Yang, Yang; Yang, Kuo; Hao, Teng; Zhu, Guodong; Ling, Ruby; Zhou, Xuezhong; Li, Ping (Frontiers in Physiology, 2018)
Objectives: Network pharmacological methods were used to investigate the underlying molecular mechanisms of LianXia NingXin (LXNX) formula, a Chinese prescription, to treat coronary heart disease (CHD) and disease phenotypes (CHD related diseases and symptoms). Methods: The different seed gene lists associated with the herbs of LXNX formula, the CHD co-morbid diseases and symptoms which were relieved by the LXNX formula (co-morbid diseases and symptoms) were curated manually from biomedical databases and published biomedical literatures. Module enrichment analysis was used to identify CHD-related disease modules in the protein-protein interaction (PPI) network which were also associated to the targets of LXNX formula (LXNX formula’s CHD modules). The molecular characteristics of LXNX formula’s CHD modules were investigated via functional enrichment analysis in terms of gene ontology and pathways. We performed shortest path analysis to explore the interactions between the drug targets of LXNX formula and CHD related disease phenotypes (e.g. co-morbid diseases and symptoms). Results: We identified two significant CHD related disease modules (i.e. M146 and M203), which were targeted by the herbs of LXNX formula. Pathway and GO term functional analysis results indicated that G-protein coupled receptor signaling pathways (GPCR) of M146 and cellular protein metabolic process of M203 are important functional pathways for the respective module. This is further confirmed by the shortest path analysis between the drug targets of LXNX formula and the aforementioned disease modules. In addition, corticotropin releasing hormone (CRH) and natriuretic peptide precursor A (NPPA) are the only two LXNX formula target proteins with the low shortest path length (on average shorter than 3) to their respective CHD module and co-morbid disease and symptom gene groups. Conclusions: G-protein coupled receptor signaling pathway and cellular protein metabolic process are the key LXNX formula’s pathways to treat CHD disease phenotypes, in which CRH and NPPA are the two key drug targets of LXNX formula. Further evidences from Chinese herb pharmacological databases indicate that Pinellia ternate (Banxia) has relatively strong adjustive functions on the two key targets.